Hukum Demonstrasi dalam Fikih Kontemporer: Analisis Saddudz Dzari’ah dan Partisipasi Perempuan pada Aksi Indonesia Gelap (Kajian atas Hasil Bahtsul Masail Pesantren Se-Jawa Madura) - Ainin Nadhifah (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2026)
This study analyzes the legal ruling on the “Indonesia Gelap” (Dark Indonesia) protest movement from the perspective of contemporary Islamic jurisprudence (fiqh), focusing on the application of sadd al-dharī‘ah (blocking the means to evil) and examining the active participation of women in public spaces. The research is based on the 21st decision of the Bahtsul Masail Forum (FBM) of Islamic boarding schools across Java and Madura (2025.) Employing a qualitative library research method with a normative-juridical approach, this study analyzes the forum’s decision text, classical fiqh books (turats), and principles of uṣūl al-fiqh. The findings reveal that the original legal status of protest is mubāḥ (permissible) as a means of amar ma‘rūf nahi munkar (enjoining good and forbidding evil), yet its permissibility is conditional. The “Indonesia Gelap” protest is deemed impermissible because the mass lights-off action potentially causes systemic harm (mafsadah), such as increased crime rates, disruption of public services, and threats to life safety. Hence, the maxim dar’u al-mafāsid muqaddam ‘alā jalb al-maṣāliḥ (preventing harm takes precedence over securing benefits) must be prioritized. Women’s participation in protests is conditionally permissible (jawāz) provided they maintain their honor (murū’ah), remain safe from fitnah and unlawful mixing (ikhtilāṭ), and obtain permission from their husbands (for married women). If the situation is unsafe, women are advised to channel their aspirations through other, more beneficial means. This study contributes to the development of contemporary fiqh siyāsah that is contextual and responsive to socio-political dynamics, offering legal guidance for society and Islamic boarding schools in responding to mass protests